Membangun Identitas Lokal Melalui Desain Multimedia: Analisis Logo Umkm Sambas - Mario Mario; Ibnu Ajan Hasibuan; Naufal Aulia Fiermeiza (CITRAKARA, 2026)
Logos play a crucial role in building the visual identity of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. Besides serving as a business identity, logos also serve as visual media that communicate cultural values ​​and local characteristics. This study aims to analyze how MSME logos in Sambas Regency represent and build local identity through multimedia design. Using a qualitative approach, this study employs Charles Sanders Peirce's semiotic framework to examine the visual elements contained in selected MSME logos. Data were collected through documentation and analyzed by identifying icons, indices, and symbols represented in the logos. The findings indicate that visual elements such as local fauna, geographical features, colors, and cultural symbols are consistently used to represent the social and cultural characteristics of Sambas. These elements not only strengthen brand identity but also serve as representations of local values ​​and community identity.